Making an Investment/Production Decision in an Uncertain Environment - Shatalova, Alevtina (E-business technologies conference proceedings, 2021)
This article presents the results of scientific research in the field of fuzzy data. Based on the developed methods, a model of making a decision on investment/production in conditions of uncertainty is described. This model includes several auxiliary models: a mathematical model of linear programming of investment project optimization, a model of the parametric α-level method of λ-continuation for the problem of fuzzy linear programming, an improved fuzzy five-factor Altman model. Conclusions and proposals of a scientific, theoretical and practical nature are also formulated.